(untitled) (Research, Society and Development, 2021)
Introduction: Fibromyalgia presents itself as a clinical rheumatological condition that is considered a chronic painful syndrome. Among the symptoms, pain, muscle fatigue, difficulty sleeping, morning stiffness and cognitive disorders stand out. Exercises can assist these individuals in preserving physical fitness and increasing endorphins, which together will provide an improvement in the quality of life of these patients. Objectives: to evaluate the types of aerobic exercises, in relation to frequency, intensity and duration and the benefits in reducing the pain threshold in fibromyalgia. Methods: the present study is a systematic review. Where searches were performed using the SciELO, PubMed, PEDro, CAPES, LILACS databases and active search of references. Studies were selected that were related to the female audience, clinical trials, and studies that have pain as the primary outcome. In English and Portuguese. Results: Studies related to aerobic exercise in patients with FM have shown benefits in reducing pain. They showed that patients who used aerobic exercise in their protocols contemplated significant gains in reducing the painful symptoms of FM. Conclusion: It is suggested that aerobic exercise as a non-medication treatment contributes to the reduction of painful symptoms in fibromyalgia patients, as long as they respect the limits of intensity, frequencies and duration of these individuals.